A interdisciplinaridade nas novas configurações curriculares da educação superior brasileira: o caso dos BI da UFBA - Gabriel Swahili Sales de Almeida (EccoS – Revista Científica)
The contemporary university has encountered social, epistemological and structural challenges that require a profound reflection on its status and social function. With the objective of understanding these new configurations, this article seeks to discuss the meanings of interdisciplinarity in the Bacharelados Interdisciplinares (Undergraduate Interdisciplinary Programs) of the Universidade Federal da Bahia (Federal University of Bahia) from a documentary research of the process of creation of these. Federal level legislation, resolutions, documents and Institutional Development Plan of UFBA and reference documents for BI were used as sources, such as the Political Pedagogical Projects, covering the period from 2006 to 2016. From the analysis, we could conclude that the absence of an institutional policy specifically focused on interdisciplinarity imposed on the BI, a project initially thought as a means of reformulating the university, that were formatted to fit the same, operating mainly on an institutional disciplinary frame.